Service delivery challenges in the provision of sustainable sanitation and clean water: the case of Capricorn District Municipality, Limpopo Province - Mabotha, Phuti Alfred Patrick (My University, 2022)
South Africa is a country experiencing water scarcity, and the provision of water as well as sanitation is a basic need and a right that must be provided to the populace by the municipalities. The water must either be subsidised by the government through the Municipal Infrastructure Grant or financed through the municipality ’s resources. The Capricorn District Municipality is composed of the Polokwane, Molemole, Lepelle Nkumpi, and Blouberg local Municipalities. Amongst all these municipalities, there is high rural domination and the inability to provide water daily in most jurisdictional areas. In achieving the objectives and addressing factors that impact negatively on sustainable supply of water and effective sanitation within Capricorn District Municipality the study adopted, the theory of rising expectations, the philosophy of servant leadership, the public choice theory, the district’s development plan, the rational model of reasoning and the participatory research paradigm because the study addresses the societal issues that affect mostly marginalised groups. The study used a mixed method research methodology that is dominated by the qualitative method. Quantitative method is used to justify availability of water and sanitation to the Capricorn District’s civilians while the qualitative method was used to investigate the cause and effect of the non-provision of sustainable water as well as sanitation. The study established that there are some hindrances that were found in the focus area (Capricorn District Municipality) because of; illicit activities, poor infrastructural maintenance, and the need to establish an enabling environment by the politicians as well as the officials with no interference in the running of the administrative affairs
Thesis (Ph.D.(Public Administration)) -- University of Limpopo, 2022
Keywords: Water; Sustainable; Municipality and the Capricorn district Municipality; Municipal water supply; Water-supply -- South Africa -- Limpopo; Sanitation; Municipal services -- South Africa -- Limpopo